Therapeutic Plasma Exchange is Safe and Efficacious in Normalizing Increased Plasma Viscosity Associated with COVID-19. (28th October 2021) - Nakahara, Hirotomo; Barker, Nicholas; Auld, Sara; Truong, Alexander; Daniels, Lisa; Friend, Sarah; Gaddh, Manila; Cobb, Jason; Connor, Michael; Polly, Derek
Abstract: Background: COVID-19 associated hyperviscosity is a potential driver for the increased rates of thrombotic complications and multi-organ failure associated with severe COVID-19. Limited experience suggests a promising role for Therapeutic Plasma Exchange (TPE) in COVID-19 management based on the hypothesis that clinical benefit is derived from reduction in plasma viscosity. However, systematic study evaluating the safety and efficacy of TPE in these patients has not been done. Objective: To evaluate the safety and efficacy of TPE in a subset of critically ill patients with COVID-19 and elevated blood viscosity in a randomized controlled trial (RCT). Study Design and Methods: This study was conducted in the intensive care units (ICUs) of 3 hospitals in our health system, with a limited initial enrollment target of 20 patients. Participants included adult COVID-19 patients with moderate elevation in plasma viscosity (2.3-3.5 centipoise) or significant hyperfibrinogenemia (>800 mg/dL) that were not improving despite standard supportive care. Patients with bacterial or fungal coinfection or moribund patients were specifically excluded. Upon enrollment, patients were randomized 1:1 to the treatment group (1 plasma volume TPE with frozen plasma (FP) replacement on 2 consecutive days) or control group (continued standard of care (SOC)). Primary measures included the safety/tolerability of TPE and change in plasma viscosity levels after TPE versus SOC. Secondary measures included evaluation of various clinical and laboratory parameters, including fibrinogen and other coagulation-related markers, mortality, bleeding and thromboembolic complications, ICU length of stay and time to discharge after enrollment. Results: Preliminary analysis of collected data demonstrates that TPE is safe and well-tolerated in these patients, with adverse events limited to one mild occurrence of tachycardia that improved upon decreasing the flow rate. There was significant decrease in plasma viscosity in the TPE treatment group, compared to the SOC control group. Secondary measures of select laboratory parameters also show a significant decrease in fibrinogen, von Willebrand factor (vWF), Factor VIII, and erythrocyte sedimentation rate in the TPE treatment group. No significant differences were seen in levels of fibrin monomer, total IgG, total IgM, total protein, or total albumin between the two groups. Data collection and analysis for clinical parameters are ongoing. Conclusions and Relevance: Here we report preliminary results suggesting that TPE is safe and effective for normalizing plasma viscosity in critically ill COVID-19 patients. Concomitant removal of large plasma proteins (fibrinogen, vWF) hints at their role in driving the increased viscosity associated with severe disease, which may contribute to clotting and end-organ damage in COVID-19. Based on lack of change in total IgG/IgM levels, TPE is not anticipated to hinder the patient's humoral immunity by removing existing anti-SARS-CoV-2 specific antibodies. These results warrant further studies on the utility of TPE to mitigate critical illness in COVID-19 patients.